2020
DOI: 10.1002/ldr.3707
|View full text |Cite
|
Sign up to set email alerts
|

Soil available nitrogen and phosphorus affected by functional bacterial community composition and diversity as ecological restoration progressed

Abstract: Available nitrogen (N) and phosphorus (P) are the most common elements limiting the success of ecosystem restoration. Soil microbial communities, harbouring the alkaline metalloprotease (apr) gene and alkaline phosphatase activity gene (phoD), play a crucial role in regulating and maintaining soil available N and P. However, the dynamics of apr-and phoD-harbouring bacteria and their contributions to regulating soil available N and P balances remain largely unexplored as ecological restoration proceeded. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 86 publications
(161 reference statements)
0
6
0
Order By: Relevance
“…In addition, SOM is always associated with multiple soil nutrients like P and N, as well SM and pH in soils, were reported to correlate with the microbial community [55,56]. Thus, we deduced that SOM improved after NVR, and then regulated soil microbial diversity by three paths via the association of SOM and other soil properties (Figure 1c).…”
Section: Nvr Influenced the Microbial Community In Gullies By The Acc...mentioning
confidence: 81%
“…In addition, SOM is always associated with multiple soil nutrients like P and N, as well SM and pH in soils, were reported to correlate with the microbial community [55,56]. Thus, we deduced that SOM improved after NVR, and then regulated soil microbial diversity by three paths via the association of SOM and other soil properties (Figure 1c).…”
Section: Nvr Influenced the Microbial Community In Gullies By The Acc...mentioning
confidence: 81%
“…PCoA analysis suggested that the microbial communities of the 10 types of grassland were clustered into three groups, indicating that different grassland types had a greater impact on the composition of microbial communities compared to degradation and restoration. A recent study showed that grassland degradation or artificial restoration changed plant coverage and soil physical and chemical properties, thereby affecting the soil bacterial community structure ( Wang H. L. et al, 2021 ). After meadow degradation, the soil moisture content and the relative abundance of Proteobacteria were significantly decreased, and Proteobacteria grew better in swamp and meadow environments with high moisture contents ( Chen et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…One of the reasons might be that the dilution effect of soil C and N accumulation on soil P could cause or intensify the P limitation in the later stage of vegetation restoration ( Groenigen et al, 2006 ). Moreover, the distinct beta diversities of the apr- and phoD- harboring bacteria could cause a steady increase in soil available N and a general decrease in available P, which may further affect the plant nutrient limitation as ecosystem restoration proceeds ( Wang et al, 2020 ; Xu et al, 2020 ). In brief, our results suggest that the nitrogen limitation of plant and microbial communities was alleviated significantly and thereafter began to shift to P limitation at the later stages of vegetation restoration, supporting our first hypothesis, which is that plant and soil microbial metabolism are more likely limited by soil P in the late restoration stages.…”
Section: Discussionmentioning
confidence: 99%